Characterisation of a β detector on positron emitters for medical applications. (November 2019) - Collamati, F.; Moretti, R.; Alunni-Solestizi, L.; Bocci, V.; Cartoni, A.; Collarino, A.; De Simoni, M.; Faccini, R.; Fischetti, M.; Giordano, A.; Maccora, D.; Mancini-Terracciano, C.; et al.
Highlights: Radio Guided Surgery (RGS) based on βradiation extends its range of application. PET radiotracers can be exploited as tumor marker enabling complete resection. RGS based on β -probe and 68 Ga-emitters is for neuroendocrine and prostate cancers. Abstract: Purpose: Radio Guided Surgery (RGS) is a technique that helps the surgeon to achieve an as complete as possible tumor resection, thanks to the intraoperative detection of particles emitted by a radio tracer that bounds to tumoral cells. In the last years, a novel approach to this technique has been proposed that, exploiting β - emitting radio tracers, overtakes some limitations of established γ -RGS. In this context, a first prototype of an intraoperative β particle detector, based on a high light yield and low density organic scintillator, has been developed and characterised on pure β - emitters, like 90 Y . The demonstrated very high efficiency to β - particles, together with the remarkable transparency to photons, suggested the possibility to use this detector also with β + emitting sources, that have plenty of applications in nuclear medicine. In this paper, we present upgrades and optimisations performed to the detector to reveal such particles. Methods: Laboratory measurement have been performed on liquid Ga 68 source, and were used to validate and tune a Monte Carlo simulation. Results: The upgraded detector has an ~ 80 % efficiency to electrons above ~ 110 keV, reaching a plateau value of ~ 95 % . At the same time, the probe is substantially transparent to photons below ~ 200 keV, reaching a plateau value of ~ 3 % . Conclusions: The new prototype seems to have promising characteristics to perform RGS also with β + emitting isotopes.